Pemberdayaan Masyarakat Desa Krajan Melalui Budidaya Jamur Tiram Mewujudkan Desa Tanpa Kemiskinan - Muhamad Firmansyah; Siti Muntahanah Ana; Esti Ningrum Esti (Indonesian Journal of Community Service and Innovation, 2025)
The Community Service Program in the form of Community Empowerment by Students (KKN-PMM), funded by the Directorate of Research and Community Service (DPPM) KemenristekDIKTI for the 2025 fiscal year, aims to enhance welfare and address socio-economic issues in Krajan Village, Pekuncen, through the development of oyster mushroom cultivation enterprises. This program is implemented to assist the "Sekar Wangi" Women's Farming Group (KWT) and "Bina Mulya 16" Youth Organization, who previously faced production challenges and unemployment. The method employed is Participatory Rural Appraisal, involving socialization, training, equipment provision, assistance, and evaluation. The primary focus is on technology transfer, particularly the Mixer Machine for Media Mixing and the Baglog Press Machine, to address the previously manual media preparation process. The outcomes of the activities indicate an improvement in the partners' understanding and skills in efficient baglog production, supported by practical use of the machines. The use of these machines enhances production efficiency, baglog quality, and business capacity, while simultaneously reducing labor costs. Additionally, post-harvest counseling and processing of mushrooms into marketable products have been conducted. The program's sustainability is supported by an MoU with Krajan Village as a Foster Village of UNWIKU. This program aligns with the achievement of the SDGs in poverty reduction and job creation.